Talent identification and development in the context of 'growing up' - Malina, R. M.; Cumming, S. P.; Coelho e Silva, M. J.; Figueiredo, A. J. (Routledge handbook of talent identification and development in sport, 2017)
The search for sport talent at relatively young ages is in many ways more prevalent and structured at present compared to the past. An important corollary is the subsequent development of talent in youth as the process is superimposed upon a constantly changing base that comprises the process of "growing up"—the demands of physical growth, biological maturation and behavioral development as youngsters pass from childhood through puberty and adolescence into adulthood. General concepts related to the three dominant processes are briefly considered. Readiness for sport is viewed from the perspective of the characteristics of youth athletes and the demands of the sport environment. Models of talent development are briefly considered with emphasis on areas and issues needing attention. Limitations of available data and assessment protocols are emphasized throughout.